Production and Characterization of High Value Prebiotics From Biorefinery-Relevant Feedstocks - Rajan, Kalavathy; D’Souza, Doris H.; Kim, Keonhee; Choi, Joseph Moon; Elder, Thomas; Carrier, Danielle Julie; Labbé, Nicole (Frontiers in Microbiology, 2021)
Hemicellulose, a structural polysaccharide and often underutilized co-product stream of biorefineries, could be used to produce prebiotic ingredients with novel functionalities. Since hot water pre-extraction is a cost-effective strategy for integrated biorefineries to partially fractionate hemicellulose and improve feedstock quality and performance for downstream operations, the approach was applied to process switchgrass, hybrid poplar and southern pine biomass at 160 °C for 60 min. As a result, different hemicellulose-rich fractions were generated and the chemical characterization studies showed that they were composed of 76 to 91% of glucan, xylan, galactan, arabinan and mannan oligosaccharides. The hot water extracts also contained minor concentrations of monomeric sugars (≤ 18%), phenolic components (≤ 1%) and other degradation products (≤ 3%), but were tested for probiotic activity without any purification. When subjected to batch fermentations by individual cultures of Lactobacillus casei, Bifidobacterium bifidum and Bacteroides fragilis, the hemicellulosic hydrolysates elicited varied responses. Switchgrass hydrolysates induced the highest cell count in L. casei at 8.6 log10 cells/mL, whereas the highest cell counts for B. fragilis and B. bifidum were obtained with southern pine (5.8 log10 cells/mL) and hybrid poplar hydrolysates (6.4 log10 cells/mL), respectively. The observed differences were attributed to the preferential consumption of mannooligosaccharides in southern pine hydrolysates by B. fragilis. L. casei preferentially consumed xylooligosaccharides in the switchgrass and southern pine hydrolysates, whereas B. bifidum consumed galactose in the hybrid poplar hydrolysates. Thus, this study 1) reveals the potential to produce prebiotic ingredients from biorefinery-relevant lignocellulosic biomass, and 2) demonstrates how the chemical composition of hemicellulose-derived sources could regulate the viability and selective proliferation of probiotic microorganisms.